A 50‐year record of nitrate concentrations in the Slapton Ley Catchment, Devon, United Kingdom. Issue 1 (29th November 2020) - Burt, Tim P.; Worrall, Fred; Howden, Nicholas J. K.; Jarvie, Helen P.; Pratt, Andrew; Hutchinson, Tom H.
Abstract: Slapton Ley, a coastal lake, is the largest natural body of fresh water in south‐west England. There was concern in the 1960s that the lake was becoming increasingly eutrophic. To quantify inputs of water, sediment and nutrients into the lake, Slapton Ley Field Centre initiated a programme of weekly water quality sampling in September 1970. Of all the chemical properties which have been measured over the decades, the nitrate record has been the subject of more research than any other. The weekly monitoring has been supplemented by research projects aimed at understanding aspects of processes and patterns of nitrate delivery to the stream network. Three aspects of the nitrate record are reviewed: short‐term process dynamics; the annual cycle of influent streams and the lake itself; and long‐term trends. In the first two decades of monitoring, there was increasing concern about a trend of rising nitrate concentrations, an issue in most lowland rivers in the United Kingdom at the time. In the 1990s, nitrate concentrations levelled off and then have fallen steadily in recent years. In relation to eutrophication, there are clear signs of improvement in the influent streams, but concerns remain about water quality in the lake itself. Abstract :